Notary Role In Determining Acceptance Or Cancellation Will The Provided In Article 194-209 Islamic Law Compilation - Jita Zahara; Ade Christian Manapa; Arief Cholil (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to: 1) To understand how the role of the Notary in determining acceptance or cancellation will set out in articles 194 to 209 Compilation of Islamic Law. 2) In order to understand what are the reasons that make a person could fail to get a will, and how the notary in dividing section will treasure for the recipient. 3) To understand what are the barriers and solutions notary role in determining the acceptance and cancellation will. The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed by descriptive analytical method.Based on the results of data analysis concluded that: 1) the role of the notary in determining the acceptance and cancellation will have to go through the will of the testator in which it was agreed between the parties involved, and should be included / dionlinekan in the Minister of Law and Human Rights No. 60 of 2016 on Procedures for Reporting Wills and Testament Application Issuance of Electronic. Because if not then the deed will be listed online does not have a strong legal force. 2) the reasons that make a person could be canceled in the will because a person or institution authorized a treasure will be, but he refused, unable to take advantage of the treasure will as possible, or other things that make him blame and convicted criminal who belong in Article 197 compilation of Islamic Law. 3) barriers and solutions in the division will was that the heirs who assumed that he did not get the part of the will so many of them impede the course of a will, and the solutions that are required in the making of a will should be through consensus among family testator with parties associated therein, which aims to avoid things that sustainable in the future.Keywords: Wills; Cancellation; Reception.